A new perspective on the relationship between the construction industry performance and the economy outcome- a literature review - Zaid Mohammed Hatem,; A. Kassem, Mukhtar; Kherun Nita Ali,; Muhamad Azry Khoiry, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The attempts to analyze the relationship between the construction industry and economic growth have integrated many different methods. The process has become to be perceived as “construction economics” analysis. It is conceptualized as a procedure where construction industries outcomes implement increasingly more relevant for nation’s development benefits throughout mostly economic interdependencies that are emphasized as financial sources. Concurring with the present-day standards for affirming an industry, in considerably most facets of analysis result interpreted on a solely economic aspect which is not a conspicuous and significant indicator for construction industry initiates through its resolution outcome. Whereas proceed competently and developed directions from scholars or experts are the determinants of success that emerge due to reviews of relevant practical and research inferences. Literature for analysis on output in the construction industry within the economics aspect is further inscribed in detail. Consequently, relocating the ideology used to examine construction activates implications on development augmentation and shifts the schemes for classifying construction output in the numerous conservative analytic techniques towards more functional delineation. Considering and optimize more relevant details in the systematic process of quantifying the construction value analysis will implicate a reflected actual and detailed results of industrial or enterprise entities on both theoretical and empirical perception for construction economics.